Lead Time and Cost Reduction in Reach Stacker Repair: A Lean Six Sigma Case Study - Rio Wahyu Prasojo; Abduh Ghani Amrullah; Didik Wahjudi; Samuel Trinata Winnyarto; Muhammad Razzaq Multazam; Leon Jonathan (Institute of Research and Community Outreach, Petra Christian University, 2025)
This study examines the application of the Lean Six Sigma DMAIC methodology to reduce repair times and operational costs in the maintenance of reach stackers at P. T. X, a container shipping company in Indonesia. It identifies the prolonged repair process, often extending to 14 days, primarily due to dependency on original equipment manufacturer suppliers and aging systems, as significant obstacles. The research emphasizes the development of an internally fabricated control system to mitigate these challenges, leading to enhanced operational independence and efficiency. The implementation of DMAIC methodology reduced repair lead time from 14 days to 3 days, achieving a cost reduction of over 90% related to previous downtime expenses caused by Kalmar control system failures. Through detailed analysis, the study highlighted factors contributing to inefficiencies, such as non-interchangeable components linked to identical stock keeping unit numbers, which exacerbated delays. The improved process involved creating tailored control systems, stockpiling essential components, and establishing standard operating procedure for maintenance. Furthermore, training programs for the maintenance team ensured competency in managing the new systems. The results indicate that integrating Lean Six Sigma methodologies with innovation in system development can greatly enhance reliability and efficiency in logistics operations. While this research primarily focused on Kalmar DRD and DRF types, it suggests potential for extending the approach to other reach stacker types. Future studies could investigate the integration of predictive maintenance technologies to improve reliability and reduce downtime in varied operational settings.